Prescription audit of corticosteroid usage in the department of dermatology at a tertiary care teaching hospital - PV, Mirshad; AK, Afzal Khan; Fasalu, Rahiman OM; TK, Mohammed Muneersha (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Corticosteroids are a group of commonly used drugs in dermatology practice whose non judicious use frequently results in undesirable and unwanted effects. Prescribing them rationally with care allows us to derive the maximum benefit out of them with minimal side effects. Methods: Retrospective analysis of 112 case files belonging to patients admitted in the department of dermatology over a period of one year was undertaken to ascertain the usage pattern of corticosteroids in relation to their potency, strength, frequency, duration, route, quantity to be applied. The data thus collected was expressed in terms of averages, ratios and proportions. Results: The total number of formulations prescribed were 929 out of which 10.8% were corticosteroids. The average number of formulations prescribed per patient was 8.29. About 78(70%) patients admitted in dermatology received corticosteroids. Topical steroids were prescribed in 50 patients (44.7 %) out of whom 36 (72%) received only topical, the remaining 14(28%) were prescribed both systemic and topical corticosteroids. Brand names were used in all cases. Highly potent corticosteroids like clobetasol, halobetasol and mometasone were prescribed to 39(50%) of all cases who received topical corticosteroids. Conclusion: The study reveals the deficiencies which exist in the present prescribing pattern of corticosteroids. Educational interventions among the doctors as well as students should be carried out to in order to promote rational drug use.